Artificial lighting and blue light in the operating room: what risks for the surgeon? - Lembo, Marco; Cannatà, Vittorio; Militello, Andrea; Ritrovato, Matteo; Zaffina, Salvatore; Derrico, Pietro; Borra, Massimo (La Medicina del Lavoro, 2015)
Background: Lighting in operating rooms must ensure conditions of visual comfort, wellbeing and safety when procedures are being carried out, so as to preserve the health of both workers and patients. Objectives: In this study we attempted to develop a methodology for specifically assessing the risk for surgeons of exposure to blue light, simulating the surgeon’s real working conditions. Visual comfort was also assessed by measuring maintained illuminance (Em) and the luminance levels in the visual task area within the operating field. Methods: Blue light exposure was measured by an OCEAN OPTICS-QE65000 spectroradiometer and a LSI-Lastem model Z-Lux radiometer, while for lighting measurements, a videophotometer and luxmeter were used. Results: Results show that the surgeons were exposed to blue light values lower than the limit of effective radiance LB= 100 W m-2 sr-1 foreseen by European Directive 2006/25/EC. For visual comfort, significant differences in illumination were observed between surrounding areas and the visual task areas, with very high luminance values measured in most of the observation points. Conclusions: In this case the measured values confirm that the workers were daily exposed to unsuitable luminance contrasts that can cause eyestrain. Given such results and considering the task analysis, we proposed to extend health surveillance to workers performing activities such as precision surgery for prolonged periods.